MODEL PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) BERBASIS MULTIKULTURAL DI PERGURUAN TINGGI - Masruri, M. Hadi (Maulana Malik Ibrahim State Islamic University Malang, 2017)
Multiculturalism is rooted in the terma of pluralism, in the sense that Islam looks at the diversity of the tribe, nation, language, culture and religion as reality, even as the media to know each other, respect, and appreciate so that created a life that is peaceful, tolerant, and peace in accordance with the terminology of Islam as a religion of peace. Islamic concept of multiculturalism is explicitly stated in the verses of the Qur'an and the Hadith of the Prophet, which outline include: attitude to appreciate yourself, menghargaioranglain attitude, the attitude of valuing natural environments and culturally, attitudes appreciate the beauty, attitude, and appreciate the beauty of the attitude of valuing integrity.